Famotidine promotes inflammation by triggering cell pyroptosis in gastric cancer cells - Jin Huang; Pingsheng Fan; Miao Liu; Chengtao Weng; Gaofei Fan; Tengyue Zhang; Xiaohong Duan; Yang Wu; Lili Tang; Guohong Yang; Yabei Liu (BMC, 2021)
Abstract Background Cell pyroptosis has been characterized by cell swelling and pro-inflammatory factors release to aggravate inflammatory reaction., such as interlukin-1 beta (IL-1β) and interlukin18 (IL-18). However, the function of famotidine, an antagonist of histamine H2-receptor antagonists, in cell pyroptosis remained unknown. Methods Real-time quantitative PCR (qPCR), western blotting (WB), LDH release assay and enzyme linked immunosorbent assay (Elisa) combined with inhibitor were performed to analyze the effect of famotidine on cell pyroptosis-related gene expression. Results In this study, we found that famotidine (300 μm) treatment led to a phenomenon of cell pyroptosis as confirmed by LDH assay. Further results showed that famotidine triggered cell pyroptosis in gastric cancer cells by activation of NLPR3 inflammasomes including ASC, Caspase-1 and NLRP, leading to enhanced IL-18, not IL-1β, mature and secretion. What's more, the results also showed GSDME, not GSDMD, was increased in response to famotidine stimulation in BGC823 and AGS cells. Mechanically, phosphorylation of ERK1/2 was drastically enhanced in present with famotidine treatment, while inhibition of ERK1/2 activity by U0126 could reverse the promotion of famotidine in IL-18 secretion. Conclusion These findings revealed a novel role of famotidine in cell pyroptosis in patients with gastric cancer, a comprehensive consideration is needed in treatment of gastric cancer.